The effectiveness of the self-study script as a didactic resource in remote teaching (Research, Society and Development, 2021)
In addition to being an emergency modality, remote teaching configures the realization of many and new pedagogical practices that, before, remained outside educational spaces – due to lack of resources or, even, due to resistance. In the public university context, this dynamic brought teachers and students into contact with new teaching and learning relationships, mediated specially by digital mobile technologies. Considering this context, this article is based on the objective of discussing the effectiveness of the “self-study script” as a didactic resource under the scope of remote teaching. Through a case study, the text describes a proposal implemented by one of the authors of this work, professor of a Language Course, in order to explore the aspects that support his pedagogical practice. The analyses, based on theoretical-methodological assumptions in the area of ​​teaching and technology, contemplate the structure of the script adopted by the teacher, as well as the perceptions of students who have made use of this material in their academic trajectory. In summary, the results point to the establishment of the self-study script as an effective practice, which, in remote teaching, allows the student to have a closer dialogue with the teacher and, at the same time, with the content.